ANALISIS IMPLEMENTASI KEBIJAKAN TINGKAT KOMPONEN DALAM NEGERI (TKDN) DAN KENAIKAN PERSENTASE PAJAK PENGHASILAN 22 TERHADAP PENURUNAN NILAI IMPOR DI INDONESIA - Caroline, Elizabeth; Wany, Eva (Media Mahardhika, 2025)
This research aims to determine the implementation of the Domestic Component Level Policy (TKDN) and the 22 Percentage Increase in Income Tax on Import Value in Indonesia. This research uses non-interactive qualitative methods with secondary data from the Central Statistics Agency which is directly related to import values and statutory regulations. This research uses a qualitative case study approach with a literature review as a literature study. The research results state that the TKDN Policy and the increase in PPh Article 22 are the right steps to reduce dependence on imports and encourage domestic industrial growth. This can be seen from the data on the value of imports from 2022-2023 which has experienced a decline.